Leite derramado, de Chico Buarque, à luz do conceito de alegoria de Walter Benjamin - Pereira, Rene Rogério (2011)
This paper offers a reading of the novel Leite derramado (2009) by Chico Buarque in light of the narrative theory of Walter Benjamin and his concept of allegory. From the diagnosis of the philosopher that the traditional form of narrative, as the art of giving advice and transmissibility of authentic experience, would be in danger of extinction, the study aims to investigate the possibility of its survival in contemporary society. To this end, the study covers two parallel paths: the critical heritage dedicated to highlighting aspects Chico Buarque ethical and aesthetic concerns that the approach of the philosopher and the concept of allegory and narrative in Walter Benjamin. The analysis of the novel picks up in the discontinuous and fragmentary account of the narrator, themes like death, memory, old age and language Eulálio, a narrator on his deathbed, whose speech followed the pattern of the more traditional grammar, in order to raise the contrasts between ancient and modern. The concept of allegory, far from following the classical rhetoric implies, in Benjamin's conception, the transplantation of an image, inscribed in a given context, and its insertion into another, that now receive new direction, creating an ambivalent tissue between said and suggestive. This is what happens to the context of a narrator archaic, based on the transmission of authentic experience, when transplanted to the modern context, adverse to narrative art. The results show that the allegorical element, as a method of composing prose Buarque, and assume a character of complaint about the treatment of death and old age in modern plays also a role of preserving the art of giving advice nowadays